Effects of contaminated feed with Aspergillus flavus on some hematological and biochemical parameters on Cyprinus carpio L. 1758: Nahla T. Mansoor, Mustafa Jawad Jalil, Anmar S. Mohammed Yahya, Lauya M. Abbas and Mohammed D. Salman - Mansoor, Nahla T. (The Iraqi Journal of Veterinary Medicine, 2018)
In this investigation the common carp, Cyprinus carpio L. 1758 was exposed to contaminated feed with Aspergillus flavus under laboratory aquarium conditions (glass ponds) for 90 days. Results revealed that the contaminated feed with (A. flavus) has significantly affect in body weight change, blood and biochemical parameters of groups fed on contaminated feed with A. flavus. Body weight changes were decreased in group feeding on contaminated feed with A. flavus in comparison with control group. The results showed decreases in RBCs, PCV% and Hb concentration but WBCs was increased in treatment fish in comparison with the control group. In addition, serum Glutamic pyruvic trans-aminase, Glutamic oxaloacetic trans-aminase and total cholesterol as compared to control showed an increase (P<0.05) in these parameters in contaminated fish but total protein was decreased in same groups. In conclusion, A. flavus is produced toxic compounds that represent a serious source of contamination in foods; this confirms the infection of aquacultures’ fishes with A. flavus. So, one should not store foods for long periods or under poor conditions, fish health problems may arise.